2020
DOI: 10.1002/elsc.202000009
|View full text |Cite
|
Sign up to set email alerts
|

Development, characterization, and application of a 2‐Compartment system to investigate the impact of pH inhomogeneities in large‐scale CHO‐based processes

Abstract: Large‐scale bioreactors for the production of monoclonal antibodies reach volumes of up to 25 000 L. With increasing bioreactor size, mixing is however affected negatively, resulting in the formation of gradients throughout the reactor. These gradients can adversely affect process performance at large scale. Since mammalian cells are sensitive to changes in pH, this study investigated the effects of pH gradients on process performance. A 2‐Compartment System was established for this purpose to expose only a fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…It has previously been shown that the exposure of cells to amplitudes of only 0.4 pH units already negatively impacts process performance. Furthermore, the number of exposed cells or the amount of added base was identified as the main culprits for impaired process performance [23]. Here the impact of smaller pH amplitudes (magnitude of 0.05 units) and of a narrow pH control without the introduction of amplitudes are investigated for cell lines A and B.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has previously been shown that the exposure of cells to amplitudes of only 0.4 pH units already negatively impacts process performance. Furthermore, the number of exposed cells or the amount of added base was identified as the main culprits for impaired process performance [23]. Here the impact of smaller pH amplitudes (magnitude of 0.05 units) and of a narrow pH control without the introduction of amplitudes are investigated for cell lines A and B.…”
Section: Resultsmentioning
confidence: 99%
“…Glucose was fed continually after its concentration dropped below 2 g L −1 to reestablish glucose levels of 2 g L −1 . The 2‐CSs were setup according to previously published work [23]. They consist of a bioreactor vessel with added outlet at the bottom and a bypass for the recirculation of the cells.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations